Perintah Kontrol Gerak Kursi Roda Elektrik Menggunakan Sensor Elektromiograf - Arizal Mujibtamala Nanda Imron; Wahyu Muldayani; Sumardi Sumardi (Jurnal Rekayasa Elektrika, 2019)
Paralysis is a disease that can limit the mobility of the sufferer. One solution that can help people with paralysis in carrying out their mobility is the use of an electric wheelchair. In this study, an electric wheelchair with specifications where the wheelchair motion control uses muscles on both arms, so that the electric wheelchair is very suitable for patients with paralysis in the legs and weak hand strength in turning the wheels from the wheelchair. The input of motion control commands is carried out through an electromyograph sensor mounted on the flexor muscle in both patients’ arms. The output of each sensor is given a threshold of 2 volts to distinguish control commands or not. When the sensor output is more than the same as the threshold, it is considered logic one and the other is considered logic zero. The method is used to interpret the output as a control command by impulse detection. The electric wheelchair movement that can be done is forward, turn right, and turn left.